Pneumococcal colonization dynamics among young children with and without respiratory symptoms during the first year of the SARS-CoV-2 pandemic - Liset Olarte; Brian Lee; Dithi Banerjee; Douglas S. Swanson; Christopher J. Harrison; Rangaraj Selvarangan (PLoS ONE, 2025)
Background Non-pharmaceutical interventions to mitigate the spread of SARS-CoV-2 were implemented across the United States in 2020. These public health measures might influence pneumococcal colonization in younger children and their subsequent risk of invasive pneumococcal disease. Our objective was to evaluate pneumococcal colonization rates in children ≤ 5 years of age with and without respiratory symptoms during the first 12 months of SARS-CoV-2 pandemic (April 2020 – March 2021). Study design This is a retrospective cross-sectional study evaluating pneumococcal colonization rates, density and serotype distribution across three study periods (April-July [Period 1], August-November [Period 2] and December-March [Period 3]) after implementation of non-pharmaceutical interventions in Kansas City, Missouri. Children aged ≤5 years with and without respiratory symptoms seeking care at Children’s Mercy Kansas City hospital system with a residual standard of care nasal mid-turbinate sample were included. The odds of pneumococcal colonization across study periods were calculated using multivariable logistic regression. Results A total of 311 children met inclusion criteria (126 symptomatic and 185 asymptomatic). The overall pneumococcal colonization (23% vs. 13%, p = 0.03) and SARS-CoV-2 positivity (34.1% vs. 17.8%, p = 0.001) rates were higher in symptomatic children than in asymptomatic children. The odds of pneumococcal colonization of symptomatic (Period 2: OR 1.09; 95% CI 0.33–3.64, and Period 3: OR 0.46; 95% CI 0.13–1.59) and asymptomatic (Period 2: OR 0.55; 95% CI 0.18–1.7, and Period 3: OR 0.37; 95% CI 0.11–1.2) children did not statistically differ across study periods. Pneumococcal colonization density was also not different across study periods among study groups. Overall, non-PCV15, non-PCV20 serotypes were the most frequently identified serotypes (56.8%). Conclusions Pneumococcal colonization rates and density did not significantly change across study periods as adherence to non-pharmaceutical interventions gradually relaxed during the first year of the SARS-CoV-2 pandemic.